2021
DOI: 10.3389/fneur.2021.744503
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neural Networks in Writer's Cramp as Determined by Graph-Theoretical Analysis

Abstract: Dystonia, a debilitating neurological movement disorder, is characterized by involuntary muscle contractions and develops from a complex pathophysiology. Graph theoretical analysis approaches have been employed to investigate functional network changes in patients with different forms of dystonia. In this study, we aimed to characterize the abnormal brain connectivity underlying writer's cramp, a focal hand dystonia. To this end, we examined functional magnetic resonance scans of 20 writer's cramp patients (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Although rarely seen in childhood, studies of focal dystonia in adults have demonstrated alterations in connectivity to the motor cortex in spasmodic dysphonia, 38 cervical dystonia, 39 and writer’s cramp. 40, 41 EEG connectivity studies have found abnormalities in the cortical electrophysiological patterns in patients with dystonia, 42 including patients with dystonic cerebral palsy. 43 Our study highlights the importance of the cortico-basal ganglia-cerebellar network in lesion-induced dystonia, through both functional and structural network involvement of these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Although rarely seen in childhood, studies of focal dystonia in adults have demonstrated alterations in connectivity to the motor cortex in spasmodic dysphonia, 38 cervical dystonia, 39 and writer’s cramp. 40, 41 EEG connectivity studies have found abnormalities in the cortical electrophysiological patterns in patients with dystonia, 42 including patients with dystonic cerebral palsy. 43 Our study highlights the importance of the cortico-basal ganglia-cerebellar network in lesion-induced dystonia, through both functional and structural network involvement of these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Writer's cramp is a common form of idiopathic, focal dystonia, which involves involuntary muscle contractions causing difficulty in writing. Neuroimaging studies in dystonia have shown evidence of cerebellar involvement [33].…”
Section: Cerebellar Involvement In Ataxia Tremor and Dystoniamentioning
confidence: 99%